Comparative assessment of acute and chronic ecotoxicity of water soluble fractions of diesel and biodiesel on Daphnia magna and Aliivibrio fischeri. (April 2019) - Müller, Juliana Braun; Melegari, Silvia Pedroso; Perreault, François; Matias, William Gerson
Abstract: The widespread use of diesel as a transportation fuel and the introduction of biodiesel into the world energy matrix increase the likelihood of aquatic contamination with these fuels. In this case, it is important to know the environmental impacts caused by water-soluble fraction (WSF) of these fuels, since it is the portion that can result in long-term impacts and affect regions far away from the location of a spill. Therefore, we evaluated and compared the aquatic ecotoxicity of the WSF of biodiesel and diesel through acute ecotoxicity tests with the aquatic microcrustacean Daphnia magna and the marine bacteria Aliivibrio fischeri, as well as chronic ecotoxicity tests with D. magna . The WSF of diesel was 2.5–4 folds more toxic than the WSF of biodiesel in acute ecotoxicity tests. Similarly, a comparison of the chronic ecotoxicity demonstrated that the WSF of diesel was more toxic than the WSF of biodiesel. WSF of diesel causes chronic effects on reproduction, longevity and growth of D. magna (NOEC was 12.5, 12.5, 6.25%, respectively), while WSF of biodiesel did not present significantly different results compared to the control for any of the parameters evaluated in any of the dilutions tested (NOEC> 25%). To the best of our knowledge, this is the first study that compares the chronic ecotoxicity of WSF of diesel and biodiesel on D. magna . Graphical abstract: Image 1 Highlights: Acute and chronic ecotoxicological effects of biodiesel and diesel WSF were evaluated. WSF of diesel exerted an acute toxicity 2.5 to 4 times higher than biodiesel WSF. WSF of diesel affected longevity, reproduction and growth of D. magna . WSF of biodiesel didn't exert chronic effects on D. magna at the dilutions tested.